Prevalence of Recovirus-Neutralizing Antibodies in Human Serum Samples - Farkas, Tibor (American Society for Microbiology, 2014)
To investigate recovirus infections and their association with zoonosis, the prevalence of the virus-neutralizing antibody against three recovirus serotypes was tested in the general population and in zookeepers. Neutralizing antibodies were detected in a significantly higher number of zookeepers than in the general population but with significantly lower titers than in macaques.